Prenatal diagnosis of the megacystis-microcolon-intestinal hypoperistalsis syndrome. - Young, I D (1989)
The ultrasonographic and necropsy findings in a male fetus with the megacystis-microcolon-intestinal hypoperistalsis syndrome are reported. The presence of vacuolation and degeneration in smooth muscle of bowel and bladder wall supports a previous suggestion that the macroscopic findings in this syndrome are the consequence of an underlying visceral myopathy. The unusual degree of severity of the findings in this fetus may explain the marked skewing of the sex ratio observed in affected liveborn infants.